The Relationship between Managers’ Overconfidence and Dividend Stickiness: The Moderating Role of Catering Incentives - Abbas Aflatooni (Pizhūhish/hā-yi ḥisābdārī-i mālī)
The phenomenon of dividend stickiness has recently attracted significant attention from researchers. However, limited domestic studies are addressing this issue. This study aims to better understand the various aspects of this phenomenon by examining the relationship between managers' overconfidence and dividend stickiness, as well as the effect of firms' catering incentives on this relationship. Utilizing data from 143 firms listed on the Tehran Stock Exchange between 2012 and 2023 (1,716 observations), this research employs a Logit regression approach with the maximum likelihood estimator, controlling for fixed effects of years and industries. The findings confirm the existence of dividend stickiness and reveal a positive and significant relationship between managers' overconfidence and dividend stickiness. Furthermore, the results indicate that an increase in firms' catering incentives weakens this relationship. Robustness tests, which include controls for macroeconomic variables and the impact of the COVID-19 pandemic using the ordered logit model and an alternative measure for the moderating variable, support the main findings and align with the concepts proposed in the Catering theory.Introduction Building upon Lintner's (1956) seminal research on dividend stickiness, various researchers have extensively explored this phenomenon (Lintner, 1956; Brav et al., 2005). Three primary explanations have been proposed to account for this phenomenon. First, dividends serve as a channel for transmitting a firm's private information (Guttman et al., 2010; Baker et al., 2016). Second, firms with stronger regulatory mechanisms or those exposed to greater agency conflicts tend to smooth dividends more (Leary & Michaely, 2011; Javakhadze et al., 2014). Third, investor preference for dividend payments encourages managers to cater to shareholders by providing dividends (Larkin et al., 2017). However, empirical evidence remains limited regarding how much differences in dividend stickiness among firms can be attributed to managerial beliefs (Deshmukh et al., 2013; Wrońska-Bukalska, 2018). Consequently, the present study aims to investigate the dividend stickiness phenomenon in Iranian firms, examine the relationship between managers' overconfidence and dividend stickiness, and assess the impact of catering incentives on the relationship between managers' overconfidence and dividend stickiness.Methods & MaterialData collection for this study was conducted using the Rahvard Novin database, the Codal website, and the Central Bank of Iran. Data analysis was performed using Stata software. The research models were estimated via Logit regression with the maximum likelihood estimator, controlling for fixed effects of years and industries. To address potential heteroscedasticity and correlation among error terms, cluster-robust standard errors were applied at the firm level. To ensure robustness to model specification and the moderator variable’s definition, robustness tests were conducted using the Ordered-Logit regression with a decile-ranked dependent variable, and the moderator variable was calculated differently. The study's population consists of 143 firms during 2012-2023 (1,716 firm-years) across 11 industries. Data from the previous three periods (2009-2011) were used to assess the values of some variables. To handle outliers, all continuous variables were winsorized at the 1st and 99th percentiles.FindingsThe results of this study reveal a positive and significant coefficient for the variable H_Capex, indicating that firms with high capital expenditures are more likely to exhibit dividend stickiness compared to other firms. Additionally, the positive and significant coefficient of the Over_Invest variable suggests that firms displaying over-investment behavior are more prone to dividend stickiness. These findings demonstrate a positive and significant relationship between managers' overconfidence and dividend stickiness, confirming that the first hypothesis of the research is not rejected. Furthermore, the negative and significant coefficient of the H_Capex×DP_firm indicates that an increase in catering incentives weakens the positive relationship between high capital expenditures and dividend stickiness. Similarly, the negative and significant coefficient of the Over_Invest×DP_firm shows that an increase in catering incentives weakens the positive relationship between over-investment and dividend stickiness. These results suggest that an increase in catering incentives mitigates the relationship between managers' overconfidence and dividend stickiness, leading to the non-rejection of the second hypothesis. The research findings remain robust when controlling for the effects of macroeconomic variables, the impact of the COVID-19 pandemic, the use of the ordered logit model, and an alternative measure for moderating variable.Conclusion & ResultsThe phenomenon of dividend stickiness has garnered attention from researchers in recent years, yet despite its significance, it has received limited attention in domestic research. This study investigates the existence of dividend stickiness in Iranian firms, examines the relationship between managers' overconfidence and dividend stickiness, and assesses the impact of catering incentives on this relationship. The research findings demonstrate that dividend stickiness is prevalent among Iranian firms, aligning with the findings of Beshkooh and Moharram Khani (2020). Furthermore, the results indicate that the phenomenon of dividend stickiness is more observable in firms with overconfident managers and that the relationship between managers' overconfidence and dividend stickiness weakens with an increase in catering incentives. These results, consistent with the findings of Baker and Wurgler (2004) and Lin and Yu (2023), align with the concepts proposed in the catering theory.